Analisis Soar Dalam Penentuan Strategi Pengembangan Pemasaran Produk Tabungan iB Marhamah Martabe Mudharabah Pada Bank Sumut Syariah KCP HM. Joni - Dhea Ayuni Rahmah; Muhammad Ramadhan; Juliana Nasution (Universitas Labuhanbatu, 2023)
The existence of Bank Sumut Syariah which was able to survive until the 17th year shows that so far the strategy carried out has been quite effective but the number of mudharabah savings customers still needs to be increased and they still have to continue to try to provide information to the public to become customers of Bank Sumut Syariah. In addition, an analysis of the business being undertaken is also needed to support the success of the plan. The analysis that will be carried out by the company in this study is SOAR analysis. The research problem is motivated by the results of observations obtained from Bank Sumut Syariah KCP H.M Joni, it can be seen that the realized value of financing is higher than the realized value of third party funds, which includes savings products, while the Marhamah Martabe Mudharabah Savings is a source of substantial funding, because it's PT. Bank SUMUT KCP Syariah H.M Joni is required to maximize its marketing strategy so that the target of increasing the number of customers expected by the bank can continue to increase every year. Field research research methods (field research) with the research location of Bank Sumut Syariah KCP H.M Joni which is located at Jalan H.M Joni No. 113, Medan. Methods of data collection using interviews, observation and documentation. While the data analysis technique used is descriptive qualitative analysis using SOAR analysis. The results of the study show that through strategic stages and SOAR analysis it shows that the strategy carried out by Bank Sumut Syariah KCP H.M Joni is quite effective in the marketing development strategy for marhamah martabe mudharabah savings, but seeing market opportunities that are still open along with the increasingly intense competition between Islamic banks, additional strategies are needed by utilizing strengths (strengths) and results (results) possessed.